Aureonitols A and B, Two New C13‐Polyketides from Chaetomium globosum, an Endophytic Fungus in Salvia miltiorrhiza. Issue 9 (6th September 2019) - Yang, Sheng‐Xiang; Zhao, Wen‐Ting; Chen, Heng‐Ye; Zhang, Lei; Liu, Ting‐Kai; Chen, He‐Ping; Yang, Jian; Yang, Xiao‐Long
Abstract: Two new C13 ‐polyketides, aureonitols A and B (1 and 2 ), along with five known compounds (3 –7 ), were isolated from the solid fermentation culture of the plant endophytic fungus Chaetomium globosum from the aerial parts of Salvia miltiorrhiza . The structures and absolute configurations of 1 and 2 were determined by comprehensive spectroscopic data analysis and computed methods. Compound 5 was found to display the remarkable antimicrobial activities against four multidrug‐resistant bacteria ( Enterococcus faecalis, Enterococcus faecium, Staphylococcus aureus, and Staphylococcus epidermidis ) with MIC values of 3.13–6.25 μg/mL (ciprofloxacin: 0.78–1.56 μg/mL), and also against all tested fungal strains with MIC values of 3.13–25 μg/mL (ketoconazole: 0.78–12.50 μg/mL). Abstract :